AN LEGAL ANALYSIS OF LEGAL BREACH OF CONTRACT FOR PROCUREMENT OF SERVICES - Bambang Fitrianto (Jurnal Scientia, 2023)
In a contract, what is agreed upon must be carried out in good faith, but sometimes things that have been agreed upon are not carried out. This research is empirical research using primary data from field research through interviews with parties related to the Procurement of Goods and Services at BUMN, North Sumatra, as well as secondary data resulting from library research. Regarding this matter, PPK has written to the provider 2 (two) times and has not received a definite answer as to the cause of the delay. For violations committed by CV. Sumber Berkah as the PPK provider gave CV a blacklist sanction. Sumber berkah as provider for 2 (two) years. To prevent legal liability, parties entering into contracts for the procurement of goods/services should be guided by and comply with the provisions of laws and regulations regarding the procurement of goods/services, and carry out what has been agreed in the contract in good faith.